Data governance: Digital product passports as a case study. Issue 1 (March 2023) - Ducuing, Charlotte; Reich, René Herbert
The circular economy ('CE') is a political goal to shift the economy towards a more circular and sustainable one. Data sharing shall close information gaps in the predominant economy and, hence, form the backbone of the transition to a CE. As part of the recent legislative proposals from the EC, "digital product passports" ('DPPs') are expected to constitute one-stop shops for such data and information delivery. The principal idea of DPPs is to provide product information to interested stakeholders within and outside the product value chain. However, many challenges arise with DPPs, in particular how to reconcile a broad (if no 'open') access to data while preserving the (legally protected) interests of certain actors, and the lack of trust concerning data use and quality between the actors. Our hypothesis are (i.) that such challenges are related to the absence of an appropriate (data) governance model for DPPs and (ii.) that data governance as a main concern within the data economy agenda could inform the regulation and operationalisation of DPPs. We analyse the – lack of - (data) governance of DPPs, both in the literature and in the recent legislative proposals from the EC. We find that data governance is significantly overlooked or considered only from a pure technological perspective (techno-solutionism), which is likely to jeopardise DPPs. As both a confirmation and a way forward, we establish connections to data governance as per the data economy agenda. In turn, the analysis of DPPs governance informs the general discussion on data governance.